Efficacy, strengths, and limitations of in-vehicle feedback technology to reduce young drivers’ risk: Recent findings from the literature - Marie Claude Ouimet (2512999) (2015)
The main goal of this presentation is to describe the current state of research in regards to in-vehicle feedback technology aimed at young drivers. Young drivers have a higher crash risk worldwide than other age groups, and the first months after licensing are the most dangerous. Several countries have achieved important crash reductions over the past years that are associated with the implementation of graduated driver licensing programs. Provisions of these primary and secondary prevention programs includes older age at licensing and driving privileges provided gradually to young drivers, such as driving at night and with young passengers. Development of in-vehicle technology, such as feedback devices, now allows easier implementation of secondary and tertiary interventions aimed at young drivers. A number of randomized controlled trials have been published and results suggest the efficacy of in-vehicle feedback devices in reducing some indices of risky behavior, such as g-force events. Research has also identified several obstacles to deployment of these devices, including acceptance by both young drivers and their parents. Results of recent studies by our research group on efficacy (N = 160) and acceptance (N = 380) of in-vehicle devices in 18-24 year old drivers, and individual factors that influence these dimensions, will be presented in light of the current research. The main discussion will address the efficacy of in-vehicle feedback technology to reduce young drivers’ risk, its strengths, limitations, and obstacles to implementation in primary, secondary, and tertiary prevention programs. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.91